Improvement of contact resistance at carbon electrode/organic semiconductor interfaces through chemical doping. (1st October 2022) - Watanabe, Kazuyoshi; Miura, Naoki; Taguchi, Hiroaki; Komatsu, Takeshi; Nosaka, Hideyuki; Okamoto, Toshihiro; Yamashita, Yu; Watanabe, Shun; Takeya, Jun
Abstract: Organic thin-film transistors (OTFTs) are promising building blocks for low cost, low-environmental load, and lightweight electronic devices. Carbon-based conductors can be potentially used as TFT electrodes. However, a concern is that the carbon electrode is unsuitable for carrier injection into organic semiconductors due to the difficulty in precise work function control. Herein, we have demonstrated that molecular dopants in carbon networks can improve carrier injection with a reasonably low contact resistance of 510 Ω·cm, which constitutes a key step in the realization of noble-metal-free electronic devices.